PENGARUH PENGAWASAN DAN DISIPLIN KERJA TEHADAP KINERJA BAGIAN PABRIK PADA PT ADEI PLATATION AND INUSTRI BENGKALIS - Idrivina '; Samsir '; Marzolina ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
Performance of employees in an organization has a very wide scope. Therefore, it is the leaders of the organization must be able to study and also analyze the factors that can affect the performance of employees in an organization. Man in life are often confronted with each other in a container either formal or informal. One of the processes that will always happen in any organization is communication process. The purpose of this study was to determine the effect of supervision and discipline of working on employee performance factory parts simultaneously and partially on the PT. Adei Plantation and Industry Bengkalis. In carrying out this study, the authors requires data and inforrnasi complete and accurate. Adapaun data types and sources of data in this study is primary data and secondary data. The population in this study is the employees who are employees of the factory at. Adei Plantation & Industries, amounting to 126 people. Sampling is done by using Slovin. While making respondents conducted by purposive sampling. Data collection techniques used in this study consisted of: Interview / interview and a list of questions / Questionnaire. While the analysis of the data used is multiple regression analysis, the coefficient derterminasi, F test and t test. Results of research conducted to know the results of monitoring, giving feedback on the improvement and perfection in execution, no longer able to trigger a change in performance. The level of supervision of employees is considered good. The level of employee discipline is good enough to affect performance. Production worker performance is good enough because the employees are not able to achieve the production targets set by the company. Although it has been carried out supervision and discipline of employees has been implemented, but the performance of employees who have not sepsifik changes to better.Keywords: Surveillance, Discipline, Employee Performance